Lack of phylogeographic structure in the endangered Pickersgill's Reed Frog; Hyperolius pickersgilli (Raw, 1982). Issue 1 (9th August 2019) - Kotze, Antoinette; Ralph, Taryn M.C.; Barrow, Lisa N.; Tarrant, Jeanne; du Preez, Louis; Madisha, M. Thabang; Dalton, Desire L
ABSTRACT: The Endangered Pickersgill's Reed Frog ( Hyperolius pickersgilli ) is endemic to South Africa and restricted to the KwaZulu-Natal (KZN) coast. The natural habitat of H. pickersgilli is limited to fragmented patches of coastal reed-bed wetland, the majority of which continues to undergo transformation and degradation caused by urbanisation, agriculture, mining and forestry. These changes have resulted in the steady reduction of suitable, quality habitat and severe fragmentation. In the current study we employed mitochondrial DNA and species-specific microsatellites markers (developed in the current study) to investigate the genetic structure and diversity of H. pickersgilli . Genetic markers revealed moderate to high levels of genetic diversity throughout the remnant groups and absence of specific phylogeographic structure among individuals sampled across twelve localities throughout the range of the species. Results from the current study indicate that gene flow between H. pickersgilli individuals is not restricted, whereby neighbouring groups may interact with each other through continued migration, thereby facilitating possible range expansion should habitat be available. However, the need for continued conservation of the H. pickersgilli population through the protection and management of its natural habitats should remain a top priority in order to conserve representative levels of genetic diversity.